THE LEARNING OF SCIENCE BASIC CONCEPT BY USING SCIENTIFIQ INQUIRY TO IMPROVE STUDENT’S THINKING, WORKING, AND SCIENTIFIC ATTITUDE ABILITIES - Wachidatul Linda Yuhanna; Raras Setyo Retno (University of Muhammadiyah Malang, 2016)
This research was a classroom action research which was conducted intwo cycles, each cycle consists of planning, implementing, observing, and reflecting. The data used was quantitative data on student observation sheet instruments. The Results of the study which were obtained from the first cycle showed about the students’ thinking skills and scientific works. They were categorized as excellent 18.18%, good 22.73%, enough 52.27%, and sufficiently less 6.82%. As for the scientific attitude with a very active category of 11.36%, 43.18% and less active 45.45%. It has not reached indicators of success, so it was necessary to cycle II. Cycle II demonstrated the excellent category 38.63%, 36.36% good, good enough18.18% and less 6.81%. While the scientific attitude in the cycle II was an active attitude 29.54%, active 54.54%, inactive 15.91%. These results show an increase from the cycle I to cycle II. The conclusion of this study were: 1) learning the basic concepts of science with scientific inquiry in students can be conducible applied.2) Learning the basic concepts of science with scientific inquiry can improve thinking ability and scientific work and students’ scientific attitude. 3) Learning the basic concepts of science with scientific inquiry be able to explore and develop student creativity in designing simple experiments which can be applied in primary schools.